Development of Mail Archive Management Information System at Lombok Tengah District Education Office - Fahmi, Hairul; Fadli, Sofiansyah; Ashari, Maulana; Ramadhon, Muhammad Syahid (JISA(Jurnal Informatika dan Sains), 2022)
The Mail Archive Management Information System at the Lombok Tengah Education Office was created for the effectiveness and efficiency of storing or managing incoming mail archives and outgoing mail archives at the Education Office. Management of mails that still use the manual method, namely by storing mail archives on folders, makes frequent errors in storage such as: loss of mails, tearing of mails and so on, as well as errors in recording and the duration of data searching. This Mail Archive Management Information System was designed and built using the waterfall method and MVC (Model View Controller) as the programming method, this information system is web-based, created using the PHP framework, namely CodeIgniter, HTML, Javascript, and CSS. As for the server, it uses a default Codeigniter local server. The management of the mail archives generated by the system is able to speed up the data searching process and is able to monitoring the amount of incoming mail, outgoing mail and the number of users using the system.